Step I : Let the **two linear equations** obtained be

a_{1}x + b_{1}y + c_{1} = 0 ....(1)

a_{2}x + b_{2}y + c_{2} = 0 ....(2)

Step II : Multiplying the given equation so as to make the co-efficients of the variable to be eliminated equal.

Step III : Add or subtract the equations so obtained in Step II, as the terms having the same co-efficients may be either of opposite or the same sign.

Step IV : Solve the equations in one varibale so obtained in Step III.

Step V : Substitute the value found in Step IV in any one of the given equations and then copmpute the value of the other variable.

**Solving Simultaneous Linear Equations in one variables****Solving a system of equations which is reducibe to a system of s****imultaneous linear equations****Equation of the form ax + by + c and bx + ay = d where a and b are not equal****Equation of the form a**_{1}x + b_{1}y + c_{1}z = d_{1}, a_{2}x + b_{2}y + c_{2}z = d_{2 }and a_{3}x + b_{3}y + c_{3}z = d_{3 }here a and b are not equal

**Solving Simultaneous Linear Equations in one variables**

Exampe: Solve the following system of linear equations by applying the method of elimination by equating the co-efficients :

(i) 4x – 3y = 4 and 2x + 4y (ii) 5x – 6y = 8 and 3x + 2y = 6

**Solution:** (i) We have the linear equations are

4x – 3y = 4 ....(1)

2x + 4y = 3 ....(2)

Let us decide to **eliminate** x from the given equation. Here, the co-efficients of x are 4 and 2 respectively. We find the L.C.M. of 4 and 2 is 4. Then, make the co-efficients of x equal to 4 in the two equations.

Multiplying equation (1) with 1 and equation (2) with 2, we get ;

4x – 3y = 4 ....(3)

4x + 8y = 6 ....(4)

Subtracting equation (4) from (3), we get ;

–11y = –2

⇒ y =

Substituting y = 2/11 in equation (1), we get;

4x – 3 × = 4

⇒ 4x – = 4

⇒ 4x = 4 +

⇒ 4x =

⇒ x =

Hence, solution of the given system of equation is :

x = , y =

(ii) We have;

5x – 6y = 8 ....(1)

3x + 2y = 6 ....(2)

Let us eliminate y from the given system of equations. The co-efficients of y in the given equations are 6 and 2 respectively. The L.C.M. of 6 and 2 is 6. We have to make the both coefficients equal to 6. So, multiplying both sides of equation (1) with 1 and equation (2) with 3, we get ;

5x – 6y = 8 ....(3)

9x + 6y = 18 ....(4)

Adding equation (3) and (4), we get ;

14x = 26 ⇒ x =

Putting x = 13/7 in equation (1), we get ;

5× – 6y = 8 ⇒ – 6y = 8

⇒ 6y = – 8 = =

⇒ y =

Hence, the solution of the system of equations is x = , y =.

Example: Solve the following system of equations by using the method of elimination by equating the co-efficients. + + 2 = 10; – + 1 = 9

**Solution:** The given system of equation is

+ + 2 = 10 ⇒ + = 8 ...(1) and

**– **+ 1- 9 ⇒ **– **= 8 ....(2)

The equation (1) can be expressed as : = 8 ⇒ 5x + 4y = 80 ....(3)

Similarly, the equation (2) can be expressed as : = 8 ⇒ 4x – 7y = 112 ....(4)

Now the new system of equations is

5x + 4y = 80 ....(5)

4x – 7y = 112 ....(6)

Now multiplying equation (5) by 4 and equation (6) by 5, we get ;

20x – 16y = 320 ....(7)

20x + 35y = 560 ....(8)

Subtracting equation (7) from (8), we get ;

y =

Putting y = in equation (5), we get ;

5x + 4 × = 80 ⇒ 5x – = 80

⇒ 5x = 80 + =

⇒ x =⇒ x =

Hence, the solution of the system of equations is, x = , y = .

**Solve the following system of linear equations by usnig the method of elimination by equating the coefficients : 3x + 4y = 25 ; 5x – 6y = – 9**

Sol. The given system of equations is

3x + 4y = 25 ....(1)

5x – 6y = – 9 ....(2)

Let us eliminate y. The coefficients of y are 4 and – 6. The LCM of 4 and 6 is 12. So, we make the coefficients of y as 12 and – 12.

Multiplying equation (1) by 3 and equation (2) by 2, we get

9x + 12y = 75 ....(3)

10x – 12y = – 18 ....(4)

Adding equation (3) and equation (4), we get

19x = 57 ⇒ x = 3.

Putting x = 3 in (1), we get,

3 × 3 + 4y = 25

⇒ 4y = 25 – 9 = 16 ⇒ y = 4

Hence, the solution is x = 3, y = 4.

**Verification :** Both the equations are satisfied by x = 3 and y = 4, which shows that the solution is correct.

**Ex.23 Solve the following system of equations : 15x + 4y = 61; 4x + 15y = 72 **

Sol. The given system of equation is

15x + 4y = 61 ....(1)

4x + 15y = 72 ....(2)

Let us eliminate y. The coefficients of y are 4 and 15. The L.C.M. of 4 and 15 is 60. So, we make the coefficients of y as 60. Multiplying (1) by 15 and (2) by 4, we get

225x + 60y = 915 ....(3)

16x + 60y = 288 ....(4)

Substracting (4) from (3), we get

209x = 627 ⇒ x = = 3

Putting x = 3 in (1), we get

15 × 3 + 4y = 61 ⇒ 45 + 4y = 61

⇒ 4y = 61 – 45 = 16 ⇒ y = = 4

Hence, the solution is x = 3, y = 4.

**Verification :** On putting x = 3 and y = 4 in the given equations, they are satisfied. Hence, the solution is correct.

**Ex.26 Solve the following system of linear equations : 2(ax – by) + (a + 4b) = 0 and 2(bx + ay) + (b – 4a) = 0**

Sol. 2ax – 2by + a + 4b = 0 .... (1)

2bx + 2ay + b – 4a = 0 .... (2)

Multiplyng (1) by b and (2) by a and subtracting, we get

2(b^{2} + a^{2}) y = 4 (a^{2} + b^{2}) ⇒ y = 2

Multiplying (1) by a and (2) by b and adding, we get

2(a^{2} + b^{2}) x + a^{2} + b^{2} = 0

⇒ 2(a^{2} + b^{2}) x = – (a^{2} + b^{2}) ⇒ x = –

Hence x = –, and y = 2

Ex.27 Solve (a – b) x + (a + b) y = a2 – 2ab – b2

(a + b) (x + y) = a2 + b2

Sol. The given system of equation is

(a – b) x + (a + b) y = a2 – 2ab – b2 ....(1)

(a + b) (x + y) = a2 + b2 ....(2)

(a + b) x + (a + b) y = a2 + b2 ....(3)

Subtracting equation (3) from equation (1), we get

(a – b) x – (a + b) x = (a2 – 2ab– b2) – (a2 + b2)

–2bx = – 2ab – 2b2

x = – = a + b

Putting the value of x in (1), we get

(a – b) (a + b) + (a + b) y = a2 – 2ab – b2

(a + b) y = a2 – 2ab – b2 – (a2 – b2)

(a + b) y = – 2ab

y =

Hence, the solution is x = a + b,

y =

If you want to give information about online courses to other students, then share it with more and more on Facebook, Twitter, Google Plus. The more the shares will be, the more students will benefit. The share buttons are given below for your convenience.

SHOW CHAPTERS